Dispersion of Fine Shrimp (Metapenaeus elegans de Man 1907) on Segara Anakan Lagoon Cilacap Central Java - Suradi Wijaya Saputra (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2008)
The research of the dispersion of fine shrimp (Metapenaeus elegans de Man 1907) was held on Segara Anakan Lagoon, Cilacap Central Java. Sampling was collected systematically during survey from February to December 2004. Based on habitat condition and the distribution of Apong (small size set net) fishing units, study area was divided into three zone : the West, Central and the East Zone. Results showed that fine shrimp caught along the year, was distributed to all Segara Anakan waters. M. elegans catched more in Donan river waters (East zone). Shrimp caught in the lagoon (West zone) was lagger in size than those collected from other zone and they were in the maturing reproductive status. Specimens caught from Tritih Kulon and west Kutawaru were reconded on the smallest. Spawning occurred along the year, with peak seasons in May. The spawning ground in the West Zone, is mainly the lagoon of East Karanganyar. Key word : M. elegans, dispersion, Segara Anakan Lagoon